Universality of photoelectron circular dichroism in the photoionization of chiral molecules. (12th October 2016) - Beaulieu, S; Ferré, A; Géneaux, R; Canonge, R; Descamps, D; Fabre, B; Fedorov, N; Légaré, F; Petit, S; Ruchon, T; Blanchet, V; Mairesse, Y; et al.
Abstract: Photoionization of chiral molecules by circularly polarized radiation gives rise to a strong forward/backward asymmetry in the photoelectron angular distribution, referred to as photoelectron circular dichroism (PECD). Here we show that PECD is a universal effect that reveals the inherent chirality of the target in all ionization regimes: single photon, multiphoton, above-threshold and tunnel ionization. These different regimes provide complementary spectroscopic information at electronic and vibrational levels. The universality of the PECD can be understood in terms of a classical picture of the ionizing process, in which electron scattering on the chiral potential under the influence of a circularly polarized electric field results in a strong forward/backward asymmetry.